The 12th Symposium on Polar Science, Program and Abstracts, Session OB - 國分, 亙彦; Kokubun, Nobuo (2021)
The 12th Symposium on Polar Science, 15–18 Nov. 2021, National Institute of Polar Research (NIPR) Research Organization of Information and Systems (ROIS) conference object